Case report: Molecular analysis of a 47,XY,+21/46,XX chimera using SNP microarray and review of literature - Charalsawadi, Chariyawan; Jaruratanasirikul, Somchit; Hnoonual, Areerat; Chantarapong, Aussanai; Sangmanee, Pornsiri; Trongnit, Sasipong; Jinawath, Natini; Limprasert, Pornprot (Frontiers in Genetics, 2022)
Chimerism is a very rare genetic finding in human. Most reported cases have a chi 46,XX/46,XY karyotype. Only three non-twin cases carrying both trisomy 21 and a normal karyotype have been reported, including two cases with a chi 47,XY,+21/46,XX karyotype and a case with a chi 47,XX,+21/46,XY karyotype. Herein we describe an additional case with a chi 47,XY,+21/46,XX karyotype. For the case, a physical examination at the age of one year revealed ambiguous genitalia with no features of Down syndrome or other malformations. Growth and developmental milestones were within normal ranges. We performed short tandem repeat (STR) and single nucleotide polymorphism (SNP) microarray analyses to attempt to identify the mechanism underlying the chimerism in this patient and the origin of the extra chromosome 21. Cytogenetic analyses of the patient’s peripheral blood revealed approximately 17% of a 47,XY,+21 lineage by G-banding karyotype analysis, 13-17% by FISH analyses of uncultured peripheral blood, and 10-15% by SNP microarray analysis. Four years later, the percentage of trisomy 21 cells had decreased to approximately 6%. SNP microarray and STR analyses revealed a single maternal and double paternal genetic contribution to the patient for the majority of the markers, including the chromosome 21 markers. The extra chromosome 21 was paternally derived and meiosis I nondisjunction likely occurred during spermatogenesis. The mechanisms underlying chimera in our case was likely fertilization two spermatozoa, one with an ovum and the other with the second polar body.